RESPON PESERTA DIDIK KELAS IV SEKOLAH DASAR TERHADAP PENGEMBANGAN LKPD PENDIDIKAN KONSERVASI TOPIK BAHASAN FLORA TAMAN NASIONAL UJUNG KULON (TNUK) PADA MATA PELAJARAN IPAS - Aisahini, Fina Darma; Andriana, Encep; Hendracipta, Nana (STKIP Persada Khatulistiwa Sintang, 2024)
Student Worksheet (LKPD) is one of the learning tools which can help and facilitate teachers in learning activities. The purpose of this study was to determine the response of students to the development of LKPD Conservation Education with the topic of flora of Ujung Kulon National Park (TNUK) in the subject of Science for grade IV Elementary School. This research was conducted at SD Negeri Kota Baru with the research subjects of grade IV students with a total of 23. The study applied descriptive research. The calculation of student responses uses a student response questionnaire, this questionnaire has several aspects, namely the aspect of interest 95%, the aspect of material 98%, the aspect of language 96%, and the aspect of benefits 96%. Thus, an average of 97% was obtained which can be interpreted as